Debt Reduction, Fiscal Adjustment, and Growth in Credit-Constrained Economies - Baldacci, Emanuele; Gupta, Sanjeev; Mulas-Granados, Carlos (Washington, D.C. : International Monetary Fund, 2013)
This paper assesses the effects of fiscal consolidations associated with public debt reduction on medium-term output growth during periods of private debt deleveraging. The analysis covers 107 countries and 79 episodes of public debt reduction driven by discretionary fiscal adjustments during 1980-2012. It shows that expenditure-based, front-loaded fiscal adjustments can dampen growth when there are credit supply restrictions. Instead, fiscal adjustments that are gradual and rely on a mix of revenue and expenditure measures can support output expansion, while reducing public debt. In this context, protecting public investment is critical for medium-term growth, as is the implementation of supply-side, productivity-enhancing reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet